2010
DOI: 10.1088/0957-4484/21/17/175104
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of multi-functional silver nanoparticles with living cells

Abstract: Silver nanoparticles (AgNPs) are widely used in household products and in medicine due to their antibacterial and to wound healing properties. In recent years, there is also an effort for their use in biomedical imaging and photothermal therapy. The primary reason behind the effort for their utility in biomedicine and therapy is their unique plasmonic properties and easy surface chemistry for a variety of functionalizations. In this study, AgNPs modified with glucose, lactose, oligonucleotides and combinations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 37 publications
5
114
0
1
Order By: Relevance
“…µg/mL), and mouse germline stem cells (10 µg/mL) (Braydich-Stollen et al, 2005;Gopinath et al, 2008;Mahmood et al, 2010). An in vitro study by Sur et al (2010) indicated that lactose-modified AgNPs enter A549 cancer cells at a higher rate compared to their entrance into L929 fibroblasts. Using an MTT assay, compared the effective concentration (EC50) values of AgNPs of different sizes (~5 nm, ~20 nm, and ~50 nm) and surface areas on different cell types (A549, HepG2, MCF-7, and SGC-7901 cells).…”
Section: Discussionmentioning
confidence: 99%
“…µg/mL), and mouse germline stem cells (10 µg/mL) (Braydich-Stollen et al, 2005;Gopinath et al, 2008;Mahmood et al, 2010). An in vitro study by Sur et al (2010) indicated that lactose-modified AgNPs enter A549 cancer cells at a higher rate compared to their entrance into L929 fibroblasts. Using an MTT assay, compared the effective concentration (EC50) values of AgNPs of different sizes (~5 nm, ~20 nm, and ~50 nm) and surface areas on different cell types (A549, HepG2, MCF-7, and SGC-7901 cells).…”
Section: Discussionmentioning
confidence: 99%
“…The nanoparticles are used both for drug delivery [3] and for therapy [4]. These treatments with nanoparticles were based on action of nanoparticles on cells [5].…”
Section: Introductionmentioning
confidence: 99%
“…65 When tested on living cells, they were captivatingly shown to have dual activity, inhibiting the growth and the division of tumour cells and their nuclei, while being biocompatible for the healthy ones. 66,67 Further recent results exemplify that silver nanoparticles with different sizes could enhance magnetic induced thermo-sensitivity of glioma cells depending on their size.…”
Section: Animal Studiesmentioning
confidence: 94%